Analisis Pengaruh Keselamatan Dan Kesehatan Kerja (K3) Terhadap Produktivitas Kerja Pada Pekerjaan Pengembangan Bandar Udara Internasional Sultan Hasanuddin Makasar - Monica, Monica; Abduh, M. Natsir; Yunus, Ahmad Yauri (Program Studi Teknik Sipil Universitas Bosowa, 2026)
The airport is one of the large-scale construction projects that creates unique challenges related to K3 management, since 2019 it has continued construction and will continue development in May 2023. There is a positive influence between the workload variable on occupational safety and health with a value of 0.351, the work knowledge variable also has a positive effect on occupational safety and health with a value of 0.341, and the last variable work environment also has a positive effect on occupational safety and health with a value of 0.294. The workload variable has a positive effect on work productivity with a value of 0.408, the work knowledge variable has a positive effect on work productivity with a value of 0.252, the work environment variable has a positive effect on productivity with a value of 0.255 and the last variable work safety and health also has a positive effect on productivity with a value of 0.345. There is a positive influence between the workload variable on work productivity through safety and health with a value of 0.121, the work knowledge variable has a positive influence on work productivity through safety and health with a value of 0.117 and the work environment variable has a positive influence on work productivity through occupational safety and health with a value 0.101.